Molecular profile of parathyroid tissues and tumours: a heterogeneous landscape - Uljanovs, Romans; Strumfa, Ilze; Bahs, Guntis; Vidusa, Liga; Merkurjeva, Kristine; Franckevica, Ivanda; Strumfs, Boriss (Polish Journal of Pathology, 2021)
Advances in laboratory diagnostics and surgical treatment of primary hyperparathyroidism have ensured solid basis for research in parathyroid pathology in order to specify key molecules in pathogenesis and morphological diagnostics of difficult cases. The aim of this study was to assess the molecular landscape and its heterogeneity in primary parathyroid hyperplasia (PPH) and adenoma, compared to carcinoma and normal glands. In a retrospective analysis of 179 surgically removed parathyroid glands (102 adenomas; 27 PPH; 45 normal glands; 5 carcinomas), expression of Ki-67, p21, p27, p53, cyclin D1, Bcl-2 protein, vimentin, cytokeratin (CK) 19, E-cadherin, CD56, CD44 and parafibromin was detected by immunohistochemistry, followed by computer-assisted assessment of mean values and heterogeneity measures. Descriptive statistics and Kruskal-Wallis test were applied. Significant differences were disclosed regarding the mean and highest fraction of Ki-67 (both p < 0.001), p21 (both p < 0.001), cyclin D1 (p = 0.002) and p27-expressing cells (p = 0.010). Proliferative lesions (PPH, adenoma and carcinoma) showed statistically significantly up-regulated CK19 (p = 0.012), decreased E-cadherin levels and distinctive patterns of vimentin. CD44, CD56 and p53 were almost absent from parathyroid tissues. All carcinomas lacked parafibromin contrasting with invariable positivity in adenomas. Remarkable heterogeneity of cell cycle markers and intermediate filaments must be accounted for in scientific studies and elaboration of diagnostic cut-offs.